The Prato Method: A Guide to the Application of Economic Evaluations in Health Professions Education Research. Issue 4 (2017) - Rivers, George; Reeves, Scott; Ilic, Dragan; Foo, Jon; Walsh, Kieran; Maloney, Stephen
Abstract : Abstract: The estimation of cost and value in health professions education should involve robust methodologies and decision tools. These methods and tools should be applied consistently and transparently, but more importantly, employed in the appropriate context depending on the availability of data, target estimates, and stakeholder focus. Best practice methodology and application of decision tools will allow for a clearer and more comprehensive understanding of the return on investment of health profession education interventions by shedding greater light on the full opportunity cost of providing programs and the value of such programs to learners and recipients of health care services more broadly. This article provides insight into the basic methods, decision tools, and key evaluation concepts that might be considered for the purpose of undertaking cost and value research in continuing education for health professionals. These methods and decision tools are based on consolidated discussions by the organizing delegates of the inaugural Symposium of the Society for Cost and Value of Health Professions Education, held in Prato, Italy, October 2015. In summary, the application of economic methods and tools used for analyzing health professions education is currently inconsistent. This article provides an overview and recommendations on the use of certain economic methods and tools when evaluating health profession education programs. It also provides a clear understanding of key evaluation concepts important for undertaking an economic review of a program.